Method for manufacturing composite cathode
The use of an alcohol solvent in the manufacturing process for composite positive electrodes forms a uniform core-shell structure, addressing moisture sensitivity and enhancing electrochemical performance, thus improving the electrical properties and reducing impurities.
Patent Information
- Application Number
- JP2024069396
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-18
- Filing Date
- 2024-04-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional manufacturing methods for composite positive electrodes using nickel-rich materials and halide solid electrolytes are prone to moisture sensitivity, leading to adverse effects on electrical performance and high impurity phases.
A method involving the use of an alcohol solvent for mixing and heat treatment to form a solid electrolyte coating, which allows for in-situ synthesis of a uniform core-shell structure, reducing moisture impact and improving electrochemical performance.
The method achieves lower production costs, enhanced solid dispersion, and improved electrochemical performance with reduced impurities, while maintaining energy efficiency and environmental benefits.
Smart Images

Figure 2025013159000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for making electrodes for batteries, and in particular to a method for making a composite positive electrode using an alcohol solvent to obtain a solid electrolyte coating to improve electrical performance. [Background technology]
[0002] In recent years, the development of all-solid-state batteries has become mainstream, taking into consideration safety and energy density. Compared to conventional lithium batteries, it is said that all-solid-state batteries have room for improvement in various aspects. Among them, regarding the positive electrode material, high nickel content positive electrode materials have the disadvantage of being very sensitive to moisture (water). In addition, regarding the solid electrolyte, how to make the thickness thinner while improving the mechanical properties is a challenging issue.
[0003] Among the types of solid electrolytes, the oxide solid electrolyte, sulfide solid electrolyte, and halide solid electrolyte are the most likely to be mass-produced. Among them, the halide solid electrolyte has characteristics such as high stability, high safety, high ionic conductivity, and low interfacial impedance, and is one of the materials that has been widely discussed in recent years. However, the halide solid electrolyte is very sensitive to moisture (water), just like high-nickel-content positive electrode materials.
[0004] In conventional manufacturing methods, a composite positive electrode is generally formed by mixing and sintering a high-nickel-content positive electrode material or a halide solid electrolyte. Compared with dry mixing, wet mixing using water as a solvent has a lower manufacturing cost and can produce a composite positive electrode with high solid dispersion, but moisture has a negative effect on the halide solid electrolyte and the high-nickel-content positive electrode material, resulting in a decrease in the electrical performance of the composite positive electrode.
[0005] The present invention has been made in view of the above circumstances, and aims to provide a method for manufacturing a composite positive electrode, which can avoid the adverse effect of moisture on the composite positive electrode and improve electrical performance by forming a solid electrolyte coating layer using an alcohol solvent in order to solve the shortcomings of the conventional art. Summary of the Invention [Problem to be solved by the invention]
[0006] The object of the present invention is to provide a method for manufacturing a composite positive electrode. The method for manufacturing a composite positive electrode includes the following steps: First, a positive electrode material, a solid electrolyte, and an alcohol solvent are mixed to form a slurry. Then, the slurry is heat-treated to form a composite positive electrode. Compared with dry mixing, wet mixing has a lower manufacturing cost, is easier to control, and can improve the solid dispersion of the composite positive electrode. Since the solid electrolyte can be dissolved in the alcohol solvent and uniformly mixed with the positive electrode material, it can be synthesized in-situ on the surface of the positive electrode material particles during the post-process heat treatment, forming composite positive electrode particles with a uniform core-shell structure and improving the electrochemical performance. By using the alcohol solvent, the adverse effect of moisture on the composite positive electrode can be avoided, and a composite positive electrode with a small impurity phase can be obtained. Before the heat treatment, the slurry is, for example, coated on a carrier, and the coated slurry is rolled to form a shape. The carrier is, for example, an anti-adhesive thin film that facilitates peeling after molding. The slurry can be, for example, coated and rolled between two carriers, where the carrier is the anti-adhesive film and the current collector, to obtain a current collector with a composite positive electrode immediately after heat treatment. The temperature of the heat treatment is, for example, 160°C to 200°C, which reduces energy consumption, saves production costs, and has environmental benefits. [Means for solving the problem]
[0007] To achieve the above object, the present invention provides a method for manufacturing a composite positive electrode, including the following steps: Step (a): providing a positive electrode material, a solid electrolyte, a conductive carbon, and an alcohol solvent, the positive electrode material including a plurality of first particles, the composition of the positive electrode material being Li[Ni a Co b Mn c Al d O2, a + b + c + d = 1, 0.8 < a ≤ 1, 0 ≤ b < 1, 0 ≤ c < 1, 0 ≤ d < 1, and the composition of the solid electrolyte being Li3InCl x F y , and x + y ≤ 6, 0 ≤ x ≤ 6, 0 ≤ y ≤ 3. Step (b): mixing the positive electrode material, the solid electrolyte, the conductive carbon, and the alcohol solvent to form a first slurry. Step (c): mixing the first slurry and a binder to form a second slurry. Step (d): heat-treating the second slurry to form a composite positive electrode, the composite positive electrode including a plurality of second particles, each of the plurality of second particles containing one of the plurality of first particles and the solid electrolyte, and the solid electrolyte covering one of the plurality of first particles. Preferably, the particle diameter of the first particles is 0.5 μm to 30 μm. Preferably, the positive electrode material includes a single-crystalline positive electrode material. Preferably, 0.85 < a ≤ 1. Preferably, the alcohol solvent includes ethanol. Preferably, the second slurry is heat-treated after being formed. Preferably, the second slurry is formed on a first carrier, and the first carrier includes a current collector or an anti-adhesion material. Preferably, the first carrier includes two first carriers, and the second slurry is formed between the two first carriers. Preferably, the second slurry is heat-treated on a second carrier, and the second carrier includes glass or metal. Preferably, the temperature of the heat treatment is 160°C to 200°C. Preferably, the time of the heat treatment is 10 minutes to 180 minutes. Preferably, the heat treatment is performed in a non-oxidizing atmosphere. Preferably, the conductive carbon comprises carbon black, carbon nanotubes, or carbon fibers. Preferably, the binder comprises polytetrafluoroethylene. [Brief description of the drawings]
[0008] [Figure 1] 1 is a flowchart of a method for producing a composite positive electrode according to an embodiment of the present invention. [Figure 2A] 1 is a SEM photograph of a first embodiment of the present invention. [Figure 2B] 1 is a SEM photograph of a first comparative example. [Figure 3A] FIG. 2 is a heat flow-temperature curve diagram of the first embodiment of the present invention. [Figure 3B] FIG. 11 is a heat flow-temperature curve diagram of the second comparative example. [Figure 4A] 1 is an X-ray diffraction pattern of the first embodiment of the present invention. [Figure 4B] 13 is an X-ray diffraction pattern of the second comparative example. [Figure 5A] FIG. 2 is a voltage-capacitance curve diagram of the first embodiment of the present invention. [Figure 5B] FIG. 5 is a voltage-capacitance curve diagram of the second embodiment of the present invention. [Figure 5C] FIG. 11 is a voltage-capacitance curve diagram of the third embodiment of the present invention. [Figure 5D] FIG. 4 is a voltage-capacitance curve diagram of the first comparative example. [Figure 5E] FIG. 11 is a voltage-capacitance curve diagram of a second comparative example. [Figure 6A] FIG. 11 is a capacitance-cycle number curve diagram of the second embodiment of the present invention. [Figure 6B] FIG. 11 is a capacitance-cycle number curve diagram of the third embodiment of the present invention. [Figure 6C] FIG. 13 is a capacitance-cycle number curve diagram of the first comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Some exemplary embodiments embodying the features and advantages of the present invention will be described in detail in the following. The present invention may be modified in various ways without departing from the scope of the present invention, and the following description and drawings are used to describe the present invention and are not intended to limit the present invention. In addition, in the detailed description of the present invention, the arrangement of a first feature on or above a second feature includes an embodiment in which the arranged first feature and the second feature are directly connected, and an embodiment in which the first feature and the second feature are not directly connected via another structure between the first feature and the second feature. In addition, the terms "first", "second", "third", etc. are used to describe different configurations described in the claims, and these configurations are not limited to the terms, and in the content related to the embodiments, although the corresponding configurations are represented by different symbols, the first configuration can be represented as the second configuration and the second configuration can be represented as the first configuration, without departing from the embodiments of the present invention. In addition, the term "and / or" means one and a plurality of related elements or all combinations thereof. In addition, the term "approximately" refers to an average value within a standard error range generally accepted by those skilled in the art. Unless expressly defined in the embodiments relating to operation / operation, all numerical ranges, amounts, values, percentages, etc. described herein (e.g., angles, durations, temperatures, operating conditions, ratios and corresponding percentages, etc.) should be understood in all embodiments by the terms "about" or "substantially". In addition, unless otherwise stated in the content, all numerical values in the present invention and claims can be taken as approximations that can be varied as necessary. For example, each parameter may be interpreted in light of at least the number of significant digits described, applying ordinary rounding rules. In addition, numerical ranges herein can be expressed as ranges from one endpoint to the other endpoint or between two endpoints. It should be noted that all ranges described herein include the endpoints unless otherwise defined.
[0010] Please refer to FIG. 1. FIG. 1 is a flowchart of a method for manufacturing a composite cathode according to an embodiment of the present invention. In this embodiment, the method for manufacturing a composite cathode includes the following steps. First, as shown in step S1, a cathode material, a solid electrolyte, a conductive carbon, and an alcohol solvent are provided (prepared). The cathode material includes a plurality of first particles. The composition of the cathode material is Li[Ni a Co b Mn c Al d O2, where a + b + c + d = 1, 0.8 < a ≤ 1, 0 ≤ b < 1, 0 ≤ c < 1, 0 ≤ d < 1. The composition of the solid electrolyte is Li3InCl x F y , and x + y ≤ 6, 0 ≤ x ≤ 6, 0 ≤ y ≤ 3. In this embodiment, the cathode material is, for example, a lithium nickel cobalt manganese oxide (NCM) material with a composition of Li[Ni a Co b Mn c O2, and a = 0.83, b = 0.12, c = 0.05, that is, the ratio of nickel, cobalt, and manganese in the lithium nickel cobalt manganese oxide material is 83:12:5. In another embodiment, the cathode material is, for example, a lithium nickel cobalt manganese aluminum oxide (NCMA) material with a composition of Li[Ni a Co b Mn c Al d O2, and a = 0.88, b = 0.06, c = 0.05, d = 0.01. In yet another embodiment, the cathode material is, for example, a lithium nickel cobalt manganese oxide (NCM) material or a lithium nickel cobalt manganese aluminum oxide (NCMA) material with different composition ratios, or a composition of Li[Ni a Co b Al d]O2 is a nickel-cobalt-lithium aluminum oxide (NCA) material. In one embodiment, the positive electrode material is, for example, a lithium nickel oxide with a composition of LiNiO2. However, the present invention is not limited thereto. In this embodiment, the positive electrode material is, for example, a single crystal positive electrode material, and the particle size of the first particles is 0.5 μm to 30 μm, and the single crystal structure and small particle size can achieve enhanced electrochemical performance of the composite positive electrode. The positive electrode material can be manufactured by solid-state synthesis or sol-gel process. However, the type, particle size, composition ratio and manufacturing process of the positive electrode material of the present invention are not limited thereto, and details are omitted here. In this embodiment, the alcohol solvent is, for example, ethanol, which has the advantages of being non-toxic, easy to obtain, and low cost. In this embodiment, the conductive carbon may be carbon nanotubes, conductive graphite, conductive carbon black, acetylene black, or vapor grown carbon fiber (VGCF), but the present invention is not limited thereto.
[0011] Next, as shown in step S2, the positive electrode material, the solid electrolyte, the conductive carbon, and the alcohol solvent are mixed to form a first slurry. Compared with dry mixing, the wet mixing is less costly, easier to control, and can improve the solid dispersion of the composite positive electrode. In addition, the solid electrolyte can be synthesized in-situ on the surface of the first particles of the positive electrode material, forming a composite positive electrode with a uniform core-shell structure and improving the electrochemical performance. Since the wet mixing is performed via the alcohol solvent, the adverse effect of moisture on the composite positive electrode can be avoided, and a composite positive electrode with a small impurity phase can be obtained.
[0012] Furthermore, as shown in step S3, the first slurry and the binder are mixed to form a second slurry. In this embodiment, the first slurry and the binder are mixed, for example, in a non-oxidizing atmosphere to avoid oxidation. During mixing, the first slurry and the binder are gradually heated, for example, from the initial room temperature to 70°C to 90°C to promote the volatilization of the alcohol solvent and form a viscous second slurry. This state is advantageous for the manufacture of a composite positive electrode in the subsequent process. In this embodiment, the binder is, for example, polytetrafluoroethylene (PTFE).
[0013] Finally, as shown in step S4, the second slurry is heat-treated to form a composite positive electrode. The composite positive electrode includes a plurality of second particles. Each of the plurality of second particles includes one of the plurality of first particles and a solid electrolyte, and the solid electrolyte covers the one of the plurality of first particles (the second particles include the first particles and a solid electrolyte, and the solid electrolyte covers the first particles). Through wet mixing and heat treatment, the solid electrolyte can be synthesized in-situ on the surface of the first particles of the positive electrode material, forming the second particles of the composite positive electrode with a uniform core-shell structure, and the electrochemical performance is improved. In this embodiment, the second slurry is heat-treated after molding. The second slurry is, for example, roll-formed on a first carrier or between two first carriers. The first carrier is a current collector (current collector) or an anti-adhesive material. In this embodiment, the second slurry is, for example, applied between two polytetrafluoroethylene (PTFE) thin films and rolled, which makes it easy to peel off after rolling for the heat treatment in the subsequent process. In another embodiment, the second slurry is, for example, applied between an aluminum foil and a polytetrafluoroethylene (PTFE) thin film and rolled, which makes it possible to directly form a current collector of a composite positive electrode after peeling and heat treatment. In this embodiment, the second slurry after molding is, for example, supported on a second carrier and heat treated. The second carrier includes, for example, glass or metal. The temperature of the heat treatment is, for example, between 160°C and 200°C, and the time is between 10 minutes and 180 minutes. Preferably, the temperature of the heat treatment is between 170°C and 190°C. This has low energy consumption, can save production costs, and has environmental benefits. The heat treatment is, for example, performed in a non-oxidizing atmosphere such as an argon atmosphere or a nitrogen atmosphere.
[0014] The manufacturing process and effects of the present invention will be described in detail below with reference to comparative examples and examples.
[0015] First Example:
[0016] The first embodiment is a composite cathode manufactured by the following method. First, a cathode material, a solid electrolyte, conductive carbon, and an alcohol solvent are provided. The cathode material is a polycrystalline cathode material and has the composition Li[Ni 0.83 Co 0.12 Mn 0.05 ]O2. In other words, the cathode material of the first embodiment is a polycrystalline lithium nickel-cobalt-manganese oxide material with a molar ratio of nickel, cobalt, and manganese of 83:12:5. The composition of the solid electrolyte is Li3InCl6. The conductive carbon is vapor grown carbon fiber (VGCF). The alcohol solvent is ethanol.
[0017] Next, the positive electrode material, solid electrolyte, conductive carbon, and alcohol solvent are mixed and pulverized to form a first slurry. Furthermore, the first slurry is mixed with a binder to form a second slurry. The binder is polytetrafluoroethylene (PTFE). The first slurry and the binder are mixed in an argon atmosphere, and during mixing, the temperature is gradually increased from room temperature (25°C) to 80°C to promote the volatilization of ethanol and form a viscous second slurry.
[0018] The second slurry is then applied between two polytetrafluoroethylene (PTFE) thin films and rolled. Finally, the second slurry is peeled off from the polytetrafluoroethylene thin films and heat-treated in a flowing argon atmosphere to form the composite positive electrode of the first embodiment. The heat treatment temperature is 180°C and the time is 120 minutes.
[0019] Example 2:
[0020] The manufacturing method of the second embodiment is generally the same as that of the first embodiment. In the second embodiment, the positive electrode material is a single crystal positive electrode material, and the composition is Li[Ni 0.83 Co 0.12 Mn 0.05 In other words, the cathode material of the second embodiment is a single crystal lithium nickel-cobalt-manganese oxide material with a molar ratio of nickel, cobalt, and manganese of 83:12:5.
[0021] Example 3:
[0022] The manufacturing method of the third embodiment is generally the same as that of the first embodiment. In the third embodiment, the cathode material is a polycrystalline cathode material, and the composition is Li[Ni 0.88 Co 0.06 Mn 0.06 In other words, the cathode material of the third embodiment is a polycrystalline lithium nickel-cobalt-manganese oxide material with a molar ratio of nickel, cobalt, and manganese of 88:6:6.
[0023] First Comparative Example:
[0024] The first comparative example is a composite positive electrode manufactured by the following method. A positive electrode material, a solid electrolyte, conductive carbon, and a binder are provided. The positive electrode material is a polycrystalline positive electrode material and has a composition of Li[Ni 0.83 Co 0.12 Mn 0.05 ]O2. In other words, the positive electrode material of the first comparative example is a polycrystalline lithium nickel-cobalt-manganese oxide material with a molar ratio of nickel, cobalt, and manganese of 83:12:5. The composition of the solid electrolyte is Li3InCl6. The conductive carbon is vapor grown carbon fiber (VGCF). The binder is polytetrafluoroethylene (PTFE).
[0025] Next, the positive electrode material, solid electrolyte, conductive carbon, and binder are mixed and pulverized, and then heat-treated to form the composite positive electrode of the first comparative example.
[0026] Second Comparative Example:
[0027] The manufacturing method of the second comparative example was generally the same as that of the first example. In the second comparative example, deionized water was used as the solvent.
[0028] Please refer to Figures 2A and 2B. Figure 2A is an SEM photograph of the first embodiment of the present invention. Figure 2B is an SEM photograph of the first comparative example of the present invention. As shown in Figures 2A and 2B, the first embodiment manufactured by wet mixing has a significantly higher solid dispersion than the first comparative example manufactured by dry mixing, that is, the conductive carbon and the binder are uniformly dispersed between the second particles.
[0029] Please refer to FIG. 3A to FIG. 3B. FIG. 3A and FIG. 3B are heat flow-temperature curves of the first embodiment and the second comparative example of the present invention. FIG. 3A and FIG. 3B are results of differential scanning calorimetry (DSC) performed on the first embodiment and the second comparative example of the present invention. As shown in the figure, in the first embodiment of wet mixing using an alcohol solvent, a change in heat flow is observed near 180°C. In contrast, in the second comparative example of wet mixing using water, a change in heat flow is observed near 220°C. In other words, the slurry obtained by wet mixing using an alcohol solvent can be heat-treated at a relatively low temperature to prepare a composite positive electrode, thereby reducing energy consumption and saving manufacturing costs. As shown in FIG. 3A, the peak value of the reaction temperature in the first embodiment of the present invention is 180°C, and the peak width is 20°C. Therefore, the temperature of the heat treatment of the present invention is preferably 170°C to 190°C.
[0030] Please refer to FIG. 4A to FIG. 4B. FIG. 4A and FIG. 4B are X-ray diffraction patterns of the first embodiment of the present invention and the second comparative example. FIG. 4A and FIG. 4B are the results of X-ray diffraction analysis of the first embodiment of the present invention and the second comparative example at a temperature of 180° C. for 60 minutes. Comparing FIG. 4A and FIG. 4B, it is clear that the X-ray diffraction pattern of the second comparative example has diffraction peaks of the (222) plane, (440) plane, and (622) plane of indium oxide (In2O3), and a diffraction peak of the (101) plane of lithium chloride (LiCl). In other words, by performing wet mixing using water as a solvent, the composite positive electrode produced contains a large amount of impurity phases of indium oxide and lithium chloride. In contrast, the pure phase of the composite positive electrode produced by wet mixing using an alcohol solvent is low.
[0031] Please refer to FIG. 5A to FIG. 5E. FIG. 5A to FIG. 5C are voltage-capacity curves obtained by measuring the button batteries manufactured in the first, second and third examples of the present invention. FIG. 5D to FIG. 5E are voltage-capacity curves obtained by measuring the button batteries manufactured in the first and second comparative examples. The positive electrode of the button battery is the composite positive electrode of the first, second and third examples, the first and second comparative examples, and the negative electrode is lithium metal. The voltage window (Voltage Window) is 2.5V to 4.4V, the charge / discharge rate (C-rate) is 0.1C, and the battery is charged by a constant current (CC) method and discharged by a constant current constant voltage (CCCV) method. The constant current constant voltage method discharge means that a constant current is maintained during discharge, and a constant voltage is maintained until the discharge is completed after the upper limit voltage is reached. The temperature for charge / discharge measurement is 55°C. As shown in Figures 5A to 5E, the discharge capacity of the first embodiment is 176 mAh / g, the discharge capacity of the second embodiment is 193 mAh / g, the discharge capacity of the third embodiment is 204 mAh / g, the discharge capacity of the first comparative example is 67.9 mAh / g, and the discharge capacity of the second comparative example is 44.4 mAh / g. This shows that the composite positive electrode manufactured by dry mixing or wet mixing using water has a relatively higher capacity than the composite positive electrode manufactured by wet mixing using an alcohol solvent. In addition, the single crystal Li[Ni 0.83 Co 0.12 Mn 0.05 The discharge capacity of the second embodiment of ]O2 is 0.83 Co 0.12 Mn 0.05 ]O2 in the first embodiment. In other words, the single crystal cathode material can further improve the capacitance performance of the composite cathode.
[0032] Please refer to FIGS. 6A to 6C. FIGS. 6A to 6C are capacitance - cycle number curve diagrams obtained by measuring button batteries manufactured in the second embodiment, the third embodiment, and the first comparative example of the present invention. The following table shows the discharge capacities and capacitance retention rates of the first cycle and the 100th cycle of button batteries manufactured in the second embodiment, the third embodiment, and the second comparative example. The positive electrode of the button battery is the composite positive electrode of the second embodiment, the third embodiment, and the first comparative example, and the negative electrode is lithium metal. As shown in FIGS. 6A to 6C and Table 1, the discharge capacity of the first cycle of the second embodiment is 192 mAh / g, the discharge capacity of the 100th cycle is 118.8 mAh / g, and the capacitance retention rate is 61.9%. The discharge capacity of the first cycle of the third embodiment is 204.9 mAh / g, the discharge capacity of the 100th cycle is 164.5 mAh / g, and the capacitance retention rate is 80.3%. The discharge capacity of the first cycle of the first comparative example is 171.5 mAh / g, and the discharge capacity began to rapidly decrease from the fourth cycle. In the eighth cycle, the capacitance dropped below 0.2 mAh / g. Thus, it can be seen that the composite positive electrode manufactured by wet mixing with an alcohol solvent has relatively high initial capacitance performance and cycle performance compared to the composite positive electrode manufactured by dry mixing. Also, compared with the second embodiment where the positive electrode material composition is Li[Ni 0.83 Co 0.12 Mn 0.05 O2, the third embodiment where the positive electrode material composition is Li[Ni 0.88 Co 0.06 Mn 0.06 O2 has excellent capacitance performance and cycle performance. In other words, the positive electrode material with the composition Li[Ni a Co b Mn c O2, 0.85 < a ≤ 1 can further improve the capacitance performance and cycle performance of the composite positive electrode. JPEG2025013159000002.jpg45164
[0033] Fourth Embodiment:
[0034] The manufacturing method of the fourth embodiment is generally the same as that of the first embodiment. In the fourth embodiment, the composition of the solid electrolyte is Li3InCl 5.19 F 0.81 It is.
[0035] Fifth Example:
[0036] The manufacturing method of the fifth embodiment is generally the same as that of the first embodiment. In the fifth embodiment, the composition of the solid electrolyte is Li3InCl 4.77 F 1.23 It is.
[0037] Sixth Example:
[0038] The manufacturing method of the sixth embodiment is generally the same as that of the first embodiment. In the sixth embodiment, the composition of the solid electrolyte is Li3InCl 4.35 F 1.65 It is.
[0039] Table 2 shows the discharge capacity of the first cycle and the 45th cycle of the button batteries manufactured in the first, fourth, fifth and sixth examples. The positive electrode of the button battery is the positive electrode material of the first, fourth, fifth and sixth examples, and the negative electrode is lithium metal. The voltage window is 2.5V to 4.4V, the charge / discharge rate (C-rate) is 0.1C, and the battery is charged by a constant current (CC) method and discharged by a constant current constant voltage (CCCV) method. The constant current constant voltage method discharge means that the current is kept constant during discharge, and the voltage is kept constant until the discharge is completed after the upper limit voltage is reached. The temperature of the charge / discharge measurement is 55°C. As shown in Table 2, the discharge capacity of the fifth embodiment with a chlorine to fluorine ratio of 4.77:1.23 at the first cycle was 196.18mAh / g, which was slightly higher than that of the first embodiment, and the discharge capacity of the fourth embodiment with a chlorine to fluorine ratio of 5.19:0.81 was 189.49mAh / g, which was slightly lower than that of the first embodiment, but the difference was not significant. At the 45th cycle, the discharge capacity of the fourth embodiment was 160.21mAh / g, which was an 8.31% increase over the discharge capacity of the first embodiment, 147.91mAh / g. The discharge capacity of the fifth embodiment was 166.90mAh / g, which was an 12.83% increase over the discharge capacity of the first embodiment, 147.91mAh / g. This shows that a solid electrolyte composed of chlorine and fluorine can significantly increase the discharge capacity of the positive electrode material, and a solid electrolyte with a chlorine to fluorine ratio of 5.3:0.7 to 4.5:1.5 can exhibit even better effects. JPEG2025013159000003.jpg58164
[0040] Table 3 shows the discharge capacity retention rate at the 45th cycle of the button batteries manufactured in the first, fourth, fifth and sixth examples. As shown in Table 3, at the 45th cycle, the discharge capacity retention rate of the fourth example was 84.55%, which was increased by 10.31% compared to the discharge capacity retention rate of the first example, which was 76.65%. The discharge capacity retention rate of the fifth example was 85.07%, which was increased by 10.98% compared to the discharge capacity retention rate of the first example, which was 76.65%. The discharge capacity retention rate of the sixth example was 78.44%, which was increased by 2.34% compared to the discharge capacity retention rate of the first example, which was 76.65%. This shows that the solid electrolyte formed using chlorine and fluorine can significantly increase the discharge capacity retention rate of the positive electrode material, and the solid electrolyte with a chlorine to fluorine ratio of 5.3:0.7 to 4.5:1.5 can exhibit a more excellent effect. JPEG2025013159000004.jpg54164
[0041] As mentioned above, the object of the present invention is to provide a method for manufacturing a composite positive electrode. The method for manufacturing a composite positive electrode includes the following steps. First, a positive electrode material, a solid electrolyte, and an alcohol solvent are mixed to form a slurry. Then, the slurry is heat-treated to form a composite positive electrode. Compared with dry mixing, wet mixing has a lower manufacturing cost, is easier to control, and can improve the solid dispersion of the composite positive electrode. In addition, the solid electrolyte is dissolved in the alcohol solvent and mixed uniformly with the positive electrode material. This allows in-situ synthesis on the surface of the positive electrode material particles during the post-process heat treatment, forming composite positive electrode particles with a uniform core-shell structure and improving the electrochemical performance. Wet mixing using an alcohol solvent can also avoid the adverse effects of water on the composite positive electrode, resulting in a composite positive electrode with fewer impurity phases. Before heat treatment, the slurry can be formed, for example, by coating on a carrier and then rolling. The carrier is, for example, an anti-adhesive thin film that facilitates removal after molding. The slurry can also be, for example, coated between two carriers and rolled to form, in which the carrier is the anti-adhesive thin film and the current collector, so that a current collector with a composite positive electrode can be obtained immediately after heat treatment. The temperature of the heat treatment is, for example, 160°C to 200°C, which reduces energy consumption, saves production costs, and has environmental benefits.
[0042] The present invention can be modified in various ways by those skilled in the art, but all such modifications are within the scope of the claims of this application. [Explanation of symbols]
[0043] S1, S2, S3, S4: Step
Claims
1. A method for producing a composite positive electrode, comprising the steps of: A cathode material, a solid electrolyte, conductive carbon, and an alcohol solvent are provided, the cathode material including a plurality of first particles, and the cathode material has a composition of Li[Ni a Co b Mn c A d ]O 2 , a+b+c+d=1, 0.8<a≦1, 0≦b<1, 0≦c<1, 0≦d<1, and the composition of the solid electrolyte is Li 3 InCl x F y and x+y≦6, 0≦x≦6, 0≦y≦3; and (b) mixing the positive electrode material, the solid electrolyte, the conductive carbon, and the alcohol solvent to form a first slurry; (c) mixing the first slurry with a binder to form a second slurry; and (d) heat-treating the second slurry to remove the alcohol solvent to form the composite positive electrode, the composite positive electrode comprising a plurality of second particles, each of the plurality of second particles comprising a first particle of the plurality of first particles and the solid electrolyte, the solid electrolyte covering the one of the plurality of first particles, and the conductive carbon and the binder being uniformly distributed among the plurality of second particles.
2. 2. The method for producing a composite positive electrode according to claim 1, wherein the particle diameter of the first particles is 0.5 μm to 30 μm.
3. The method of claim 1 , wherein the positive electrode material comprises a single crystal positive electrode material.
4. 2. The method for producing a composite positive electrode according to claim 1, wherein 0.85<a≦1.
5. The method of claim 1 , wherein the alcohol solvent comprises ethanol.
6. The method of claim 1 , wherein the second slurry is heat treated after molding.
7. 7. The method of claim 6, wherein the second slurry is cast onto a first carrier, the first carrier including a current collector or an anti-blocking material.
8. 8. The method of claim 7, wherein the first carrier comprises two first carriers, and the second slurry is molded between the two first carriers.
9. 2. The method of claim 1, wherein the second slurry is heat treated onto a second carrier, the second carrier comprising glass or metal.
10. 2. The method for producing a composite positive electrode according to claim 1, wherein the temperature of the heat treatment is 160° C. to 200° C.
11. 2. The method for producing a composite positive electrode according to claim 1, wherein the heat treatment time is 10 minutes to 180 minutes.
12. The method for producing a composite positive electrode according to claim 1 , wherein the heat treatment is carried out in a non-oxidizing atmosphere.
13. The method for manufacturing a composite positive electrode according to claim 1 , wherein the conductive carbon comprises carbon black, carbon nanotubes or carbon fibers.
14. The method of claim 1 , wherein the binder comprises polytetrafluoroethylene.
Citation Information
Patent Citations
Nonaqueous electrolyte for battery, lithium secondary battery precursor, lithium secondary battery, and manufacturing method of lithium secondary battery
JP2021101432A
Lithium secondary battery solid electrolyte material, electrode and battery
JP2022531271A
Positive electrode for lithium-ion secondary battery, and lithium-ion secondary battery
WO2020261879A1